2020
DOI: 10.3390/su12052012
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Non-Point Source Pollution under Different Land Use Types

Abstract: Non-point source pollution (NPSP) is a major challenge for current global water resources. The output characteristics of pollutants under different land use types are very important for controlling NPSP. In this study, long-term positioning monitoring and an analysis of rainfall runoff from different land use types were used to evaluate a typical watershed in the water source area of the middle route of the South-to-North Water Diversion Project (MR-SNWDP). The results show significant differences in nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 29 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…In addition, a number of medium-and short-term development goals, such as water saving and conservation projects or technological measures for water resource exploitation, utilization, reasonable allocation, and control, should be adjusted in a timely manner through a series of response measures by both the government and the water authorities of Beijing. Specifically, from the point of social factors, the deconstruction of the noncapital functions of Beijing should be implemented continuously, since the effects of population reduction are conspicuous; in an economic development aspect, a great promotion in the deep transformations of the development pattern, restructured economy, and upgrading of the industrial structure to reduce the industrial scale involved in high water consumption and high pollution are essential; from the perspectives of scientific and technological factors, measures aimed at improving the water usage efficiency in the industry and agriculture, increasing the ratio of wastewater treatments, controlling the emissions of agricultural nonpoint source nutrients, and improving the comprehensive utilization capacity of rain should be upgraded [97][98][99][100]. Moreover, the consciousness of saving water should be established deeply by educating and propagating in the cultural aspects [101].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of medium-and short-term development goals, such as water saving and conservation projects or technological measures for water resource exploitation, utilization, reasonable allocation, and control, should be adjusted in a timely manner through a series of response measures by both the government and the water authorities of Beijing. Specifically, from the point of social factors, the deconstruction of the noncapital functions of Beijing should be implemented continuously, since the effects of population reduction are conspicuous; in an economic development aspect, a great promotion in the deep transformations of the development pattern, restructured economy, and upgrading of the industrial structure to reduce the industrial scale involved in high water consumption and high pollution are essential; from the perspectives of scientific and technological factors, measures aimed at improving the water usage efficiency in the industry and agriculture, increasing the ratio of wastewater treatments, controlling the emissions of agricultural nonpoint source nutrients, and improving the comprehensive utilization capacity of rain should be upgraded [97][98][99][100]. Moreover, the consciousness of saving water should be established deeply by educating and propagating in the cultural aspects [101].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate is highly mobile and leachable. It has been established that excessive application of N leads to nitrate pollution of groundwater and surface water [19,20]. Phosphorus can be transported to water bodies via storm run-off in dissolved and particulate forms [2].…”
Section: Introductionmentioning
confidence: 99%
“…NO3is low toxic but it might endogenously convert to nitrite (NO2 -), which becomes toxic to human health and aquatic organisms [33, 34, and 35]. Nitrogenous fertilizers from non-point source pollution is critical in ecosystem [36] and in agro-ecosystems, surface water pollution was strictly related to agricultural action. The result indicated that there were significant differences in total phosphorus and ortho-P content among the studied villages and between two agricultural practices in wet season.…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%